The Relation of On-Ice and Off-Ice Performance at Two Different Performance Levels in Youth Ice-Hockey Players - Roczniok, Robert; Stastny, Petr; Novak, Dominik; Opáth, Lukáš; Terbalyan, Artur; Musalek, Martin (Journal of human kinetics, 2024)
Ice hockey requires two levels of specific agility, involving different abilities, where the level of agility and their constraints might vary by the performance level. Therefore, this study aimed to compare the relationship level between on-ice and off-ice change of directional speed (COD) of youth hockey players at two performance levels. The study was conducted during the hockey season, including U16 elite players (n = 40) and U16 sub-elite players (n = 23). Both groups performed specific on-ice fitness tests (4-m acceleration, 30-m sprint, and 6 x 54-m tests, an on-ice Illinois agility test with and without a puck) and off-ice tests consisting of non-arm swing countermovement jumps (CMJs), broad jumps, and pull-ups. Pearson correlation showed that the acceleration performance of elite players was related to the CMJ (r = -0.46) and the broad jump (r = -0.31). Sub-elite players showed stronger dependence of the 30-m sprint on the CMJ (r = -0.77) and the broad jump (r = -0.43), the relation of pulls ups (r = -0.62) and the CMJ (r = -0.50) to the 6 x 54-m test, yet no association to acceleration. Elite players differ between off-ice and on-ice performance constraints, where their skating sprint is less related to their vertical and horizontal take-off abilities than in sub-elite players. Sub-elite players' off-ice power determines their sprint and repeated sprint performance. COD performance of elite and sub-elite players is based on different conditioning constraints.